Analisis penerapan koreksi fiskal atas laporan keuangan komersial untuk menghitung pajak penghasilan terutang pada CV. Kombos Tendean Manado - Mardjun, Geofanny Andreas; Sabijono, Harijanto (Yayasan Widyantara Nawasena Raharja, 2025)
This study examines the implementation of fiscal corrections in commercial financial statements to determine corporate income tax payable at CV Kombos Tendean Manado, a company engaged in four-wheeled vehicle maintenance and repair. The issue arises because the company prepares only commercial financial statements without performing fiscal corrections, potentially leading to inaccurate tax reporting. A descriptive qualitative approach was applied, with data collected through interviews and documentation. The results reveal that several expense accounts, such as telephone, electricity, business travel, inventory maintenance, and interest income require fiscal adjustments based on Indonesian tax regulations. After these adjustments, taxable income increased by IDR 2,613,707 compared to commercial profit, resulting in an additional corporate income tax of IDR 302,798. These findings emphasize that the absence of fiscal corrections can cause underpayment of tax obligations and administrative sanctions. Therefore, fiscal correction is essential to ensure compliance, financial accuracy, and corporate accountability.